Pendampingan Program Desa Wisata untuk Meningkatkan Kesejahteraan Masyarakat di Desa Trayu Kecamatan Singorojo Kabupaten Kendal - Hilwa Widad; Ahmad Faqih; Agus Riyadi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Community mentoring is a strategic approach to rural development that places the community as the primary subject, particularly in developing tourism villages based on local potential. Method: This community service activity uses a participatory approach grounded in community-based tourism, with stages of outreach, training, mentoring, and evaluation, actively involving the community at every step of the process. Results: The mentoring results indicate an increase in community understanding and capacity in managing tourism villages. Communities have begun to actively participate in tourism activities; local institutions, such as the Tourism Group (Pokdarwis), have been formed; and tourism-based economic enterprises, such as culinary and other tourism support services, have developed. Furthermore, community participation in tourism village management has also increased, although the economic impact has not been felt evenly. Conclusion: Community mentoring through the tourism village program can encourage increased community capacity, participation, and economic activity. However, ongoing mentoring and support from various parties are needed for optimal and sustainable development of tourism villages.